Contemporary Communication Model of Consumer Behaviour of Generation C - Dijana Vukovic\'; Samanta Kocijan; Ana Globocnik Zunac (ENTRENOVA - ENTerprise REsearch InNOVAtion, 2023)
Fast network communication has been manifested in recent years as an indispensable result of constant network connectivity, a common characteristic of Generation C. Through this network communication, which is particularly popular on social networks, members of this generation share and seek various experiences and information. As modern society is highly consumerist, this kind of communication is very often based on buying and using certain products, which gives its participants the role of (potential) consumers. As mentioned above, there are severe changes in the process of making consumer decisions, especially in evaluating alternatives. Fast network communication and the exchange of experiences raised consumer expectations to a higher level and influenced consumer standards and caution, but still. However, at first, it can be seen here that the modern consumer of Generation C is more educated, informed and cautious; impulsive buying, under the influence of online "hype", could be more frequent than ever. The paper aims to determine if searching for information on social media while evaluating alternatives among Generation C members affects realising impulsive purchases. Modern, connected consumers of Generation C are characterised by a specific communication model of consumer behaviour and the effects of consumer behaviour that such a model produces.
Keywords: M30; 330; generation C; consumer behavior; communication; social networks